2015
DOI: 10.1021/acs.nanolett.5b02733
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Strain Fields in GaAs/GaAsP Core–Shell Nanowires with Nanometer Resolution

Abstract: We report the nanoscale quantification of strain in GaAs/GaAsP core-shell nanowires. By tracking the shifting of higher-order Laue zone (HOLZ) lines in convergent beam electron diffraction patterns, we observe unique variations in HOLZ line separation along different facets of the core-shell structure, demonstrating the nonuniform strain fields created by the heterointerface. Furthermore, through the use of continuum mechanical modeling and Bloch wave analysis we calculate expected HOLZ line shift behavior, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…2f for x=0.25 and x=0.75 (see Supporting Information S4 for x=0.50, x=1 and for more details). A six-fold symmetry is clearly present, with six pockets at lower strain in the shell caused by the geometric relaxation induced by the six corners, in agreement with previous studies 41 . This phenomenon results in a much lower average hydrostatic strain (less than one third) than expected for a corresponding planar ሼ11 ത 00ሽ heterostructure with identical lattice mismatch as reported in Table 1.…”
Section: The Resulting Structures Have Been Characterized By Scanning Electronsupporting
confidence: 91%
“…2f for x=0.25 and x=0.75 (see Supporting Information S4 for x=0.50, x=1 and for more details). A six-fold symmetry is clearly present, with six pockets at lower strain in the shell caused by the geometric relaxation induced by the six corners, in agreement with previous studies 41 . This phenomenon results in a much lower average hydrostatic strain (less than one third) than expected for a corresponding planar ሼ11 ത 00ሽ heterostructure with identical lattice mismatch as reported in Table 1.…”
Section: The Resulting Structures Have Been Characterized By Scanning Electronsupporting
confidence: 91%
“…While the observed strain has been reported to produce shifts of only a few meV in the bandgap energy [28], consistent with the lack of noticeable shifts in the excitonic PL component and its phonon replica when changing w (figure 6), it can be large enough to produce strong effects at the MgO/ZnO interface [29]. Such inhomogeneous strain, which partially relaxes far from interfaces, has been very recently measured using a focused x-ray beam diffraction technique for another core/shell hexagonal wurtzite NW system (GaN/InGaN) [30].…”
Section: Increasing the Mgo Shell Widthsupporting
confidence: 66%
“…In the nanowire geometry, two materials of largely different lattice constants can be epitaxially grown together to form a coherently strained crystalline heterostructure, containing the same number of atomic planes in both the core and the shell [14][15][16][17][18][19][20][21][22][29][30][31][32][33][34][35][36]. Methods for spatially resolved measurements of strain in single nanowires, such as convergent beam electron diffraction [37] and focused synchrotron X-ray beam techniques [38], have recently emerged. Investigations of the critical shell thickness for coherent strain in coreshell nanowires have confirmed that the critical thickness is larger than that of a corresponding layer thickness grown on a planar substrate, as predicted by theoretical models [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The coherently strained core-shell nanowires demonstrated in this work offer the potentials for use in constructing novel optoelectronic devices and for development of piezoelectric photovoltaic devices. positions of the group-III and group-V atomic layers, which has potential use in making novel photovoltaic devices [36][37][38][39][40][41][42]. Other uses of the effects of coherent strain in core-shell nanowires include strain induced bandgap tuning [18,30,33,34,43] and increased carrier mobilities [33].Here we report on epitaxial growth of wurtzite (WZ) InAsP-InP core-shell nanowires in a series of shell thicknesses and measurements of strain and optical properties of the nanowires.These materials are of great interest for high speed infrared optoelectronics operated in the telecommunication wavelength window (1.3-1.5 µm), since the bandgap of InAsP can be tuned by compositions from 0.35 to 1.34 eV, corresponding to optical wavelengths from 3.5 µm to 0.9 µm.The WZ InAsP-InP core-shell nanowires are grown by metal-organic vapor phase epitaxy (MOVPE).…”
mentioning
confidence: 99%
See 1 more Smart Citation